2022
DOI: 10.1101/2022.02.24.481621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myelin lipids as nervous system energy reserves

Abstract: Neuronal functions and impulse propagation depend on the continuous supply of glucose1,2. Surprisingly, the mammalian brain has no obvious energy stores, except for astroglial glycogen granules3. Oligodendrocytes make myelin for rapid axonal impulse conduction4 and also support axons metabolically with lactate5-7. Here, we show that myelin itself, a lipid-rich membrane compartment, becomes a local energy reserve when glucose is lacking. In the mouse optic nerve, a model white matter tract, oligodendrocytes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The primary function of myelin is thought to be insulation of the axon, to allow fast signal conduction. Interestingly, Asadollahi et al show that myelin can also be used as energy storage under conditions of carbohydrate restriction 37 . Here, mouse oligodendrocytes use β-oxidation to maintain energy homeostasis in the optic nerve at the expense of myelin thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary function of myelin is thought to be insulation of the axon, to allow fast signal conduction. Interestingly, Asadollahi et al show that myelin can also be used as energy storage under conditions of carbohydrate restriction 37 . Here, mouse oligodendrocytes use β-oxidation to maintain energy homeostasis in the optic nerve at the expense of myelin thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Here, mouse oligodendrocytes use β-oxidation to maintain energy homeostasis in the optic nerve at the expense of myelin thickness. Also, oligodendrocyte-specific knockout of Glut1, limiting glucose uptake, leads to a reduction in myelin thickness in vivo 37 . In addition, MRI scans of patients suffering from anorexia nervosa show a loss of white matter, indicating that severe nutrient restriction in humans can also cause oligodendrocytes to metabolize lipids stored in the myelin sheath to maintain cerebral energy homeostasis 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…For constant myelination to occur, there needs to be a constant synthesis of lipids which are supplied by oligodendrocytes. Lipid metabolites can also serve as energy reserves when facing low glucose conditions [ 91 ]. The autophagy-lysosomal pathway is responsible for recycling myelin lipids which results in the release of fatty acids that can be used to produce new myelin lipids [ 69 ].…”
Section: Metabolic Profile Of Oligodendroglia and Myelin: A Brief Ins...mentioning
confidence: 99%
“…In addition, under conditions of significant energy restriction, oligodendrocytes assist axons by metabolizing myelin lipids via βOX and production of KBs. Studies conducted on a mouse optic nerve model demonstrated that generating ATP from lipids allows for greater allocation of glucose-derived metabolites to the axons, thereby preserving them [ 41 ]. Increased FAO levels were demonstrated in microglia during glucose deprivation.…”
Section: Introductionmentioning
confidence: 99%